Public attitudes toward prison capacity expansion in Mississippi - Robertson, Craig T. (American journal of criminal justice, 1994)
This paper presents the results of an exploratory study designed to identify and determine the effects of social and economic factors on Mississippians’ attitudes toward prison expansion strategies. Data were obtained from a statewide survey, utilizing a random digit dialing telephone sampling procedure. The study sample consists of 606 respondents. Favorable attitudes toward correctional facilities were hypothesized to be explained by fear of crime, presence of an existing facility, perceived economic impact of prisons, gender, race, age, and income. The results of the regression analysis revealed that the presence of an existing prison facility, perceived economic benefits, race, and education were significant predictors of attitudes toward prison expansion strategies among Mississippians. Possible explanations for the findings and directions for future research are discussed.